Na(+)/K(+)-ATPase Expression Changes in the Rabbit Lacrimal Glands During Pregnancy - Huang, Jianyan (2012)
PURPOSE: To investigate the expressional changes of Na(+)/K(+)-ATPase subunits in the lacrimal glands (LG) of term pregnant rabbits. METHODS: LG were obtained from term pregnant rabbits and age-matched female control rabbits for laser capture microdissection (LCM), real time RT-PCR, western blot, and immunofluorescence. The mRNA and proteins of α1, α2, β1, β2, and β3 subunits of Na(+)/K(+)-ATPase were detected and quantified. RESULTS: Although only the mRNA for β3 from whole LG of pregnant rabbits was significantly different from that of normal controls, many mRNA levels for α1, α2, β1, β2, and β3 from acini and epithelial cells from various duct segments that were collected by LCM were significantly different from those of normal control rabbits. Western blots demonstrated that the expressions of all three β subunits were significantly higher in pregnant rabbits, while both α subunits remained unchanged during pregnancy. Interestingly, immunofluorescence results showed that the distribution patterns of all Na(+)/K(+)-ATPase subunits during pregnancy were similar to those of the control rabbits. CONCLUSIONS: Changes were found in mRNA and protein expressions of Na(+)/K(+)-ATPase subunits in LG from term pregnant rabbits and these changes suggest a role in the pregnancy-related LG secretion changes and dry eye symptoms observed in these animals.